A 2-opt guided discrete antlion optimization algorithm for multi-depot vehicle routing problem - Barma, Partha Sarathi; Dutta, Joydeep; Mukherjee, Anupam (Decision Making: Applications in Management and Engineering, 2019)
The Multi-depot vehicle routing problem (MDVRP) is a real-world variant of the vehicle routing problem (VRP) where the customers are getting service from some depots. The main target of MDVRP is to find the route plan of each vehicle for all the depots to fulfill the demands of all the customers, as well as that, needs the least distance to travel. Here all the vehicles start from different depots and return to the same after serving the customers in its route. In MDVRP each customer node must be served by only one vehicle which starts from any of the depots. In this paper, we have considered a homogeneous fleet of vehicles. Here a bio-inspired meta-heuristic method named Discrete Antli-on Optimization algorithm (DALO) followed by the 2-opt algorithm for local searching is used to minimize the total routing distance of the MDVRP. The comparison with the Genetic Algorithm, Ant colony optimization, and known best solutions is also discussed and analyzed.